Syntheses and structures of dinuclear zinc(II) acetate-bridged coordination compounds with the aromatic Schiff base chelators N,N-dimethyl-2-[phenyl(pyridin-2-yl)methylidene]hydrazine-1-carbothioamide and N-ethyl-2-[phenyl(pyridin-2-yl)methylidene]hydrazine-1-carbothioamide - Christian S. Parry; Alex R. Abraham; Samuel K. Kwofie; Michael D. Wilson; Timothy R. Ramadhar; Raymond J. Butcher (Acta Crystallographica Section E: Crystallographic Communications, 2025)
In the centrosymmetric title complexes, di-μ-acetato-bis({N,N-dimethyl-2-[phenyl(pyridin-2-yl)methylidene]hydrazine-1-carbothioamidato}zinc(II)), [Zn2(C15H15N4S)2(C2H3O2)2] (I), and di-μ-acetato-bis({N-ethyl-2-[phenyl(pyridin-2-yl)methylidene]hydrazine-1-carbothioamidato}zinc(II)), [Zn2(C16H17N4S)2(C2H3O2)2] (II), the zinc ions are chelated by the N,N,S-tridentate ligands and bridged by pairs of acetate ions. The acetate ion in (I) is disordered over two orientations in a 0.756 (6):0.244 (6) ratio, leading to different zinc coordination modes for the major (5-coordinate) and minor (6-coordinate) disorder components. Geometrical indices [τ5 = 0.32 and 0.30 for (I) (major component) and (II), respectively] suggest the zinc coordination in these phases to be distorted square pyramidal. This study forms part of our aim to discern the mechanism of metal binding in these chelators, their specificity and selectivity, and to gain insight into the role of cellular zinc in physiological processes such as infection, immunity and cancer.